Detecting Atypical Values and Their Influence on Blast-Induced Seismic Measurement Results - Siniša Stanković; Mateja Katalinić; Dalibor Kuhinek; Vječislav Bohanek (Applied Sciences, 2022)
Blasting is an essential part of any mining or civil engineering project along with all the benefits that it brings, such as cost and time effectiveness, and safety. Still, there are a few downsides to blasting. Ground oscillation velocity as the most significant impact of blasting has been studied broadly. However, not all measured values should be used for PPV (peak particle velocity) predictor or model development. If a false measured value is included in the model or predictor development, it will provide erroneous results that can lead to the damage of the surrounding structures or an increase in the cost of blasting works. There is no clearly defined procedure for separating atypical values (outliers) within blast-induced seismic-effects measurement data. This paper recommends how to properly validate vibration velocity data by detecting and excluding atypical values and how it influences blast-induced seismic measurement results.